The appearance of a new phenomenon in geographic thinking: the influence of ICT - Róbert Sinka (Netcom)
In the last few years the effects of ICT in building knowledge based society, especially the geographical aspect of ICT became one of the major foci of academic research. The effects of technological developments and, the benefits of applying ICT techniques have influenced our geographic knowledge and thinking as well. Emphasising the quantitative and qualitative peculiarities of that knowledge, geographers have to alter some classical analytical approaches and use new methods, ideology and typology. In this present paper my aim is to give a brief summary of the most important historic milestones that could have influenced geographical thinking.